Recurrent Acute Pancreatitis: Dangerous Etiology? - Jesús Espinel Diez; Maria Eugenia Pinedo Ramos; Vanesa Ojeda Marrero; Maria Guerra del Rio Lang-Lenton (Pancreas, 2016)
Acute pancreatitis (AP) is a disorder clinically characterized by upper abdominal pain and elevated levels of pancreatic enzymes in the blood.1 After an initial evaluation, up to 10-30% of patients with AP are diagnosed with idiopathic acute pancre-atitis.2 Clinical history and conventional diagnostic tests such as blood chemistry, ultrasound (US), computed tomography (CT) scan, magnetic resonance cholangio-pancreatography (MRCP) and endoscopic ultrasonography (EUS) usually discover most causes of the recurrent acute pancreatitis (RAP). Occasionally, the first presentation, in adult patients, with pancreatic cancer (PC) is with RAP.3 We should bear this in mind.